2015
DOI: 10.4067/s0034-98872015000500008
|View full text |Cite
|
Sign up to set email alerts
|

Costo de la polifarmacia en el paciente con diabetes mellitus tipo 2

Abstract: Medications represent less than 50% of total expenses of diabetic patients with polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
9
0
3
Order By: Relevance
“…Some studies also included other medicines: antibiotics35; pain relief/anti-inflammatory drugs35; gliflozin class drugs68; sulfonylureas68 69; metformin combinations (with glibenclamide,46 with DPP4i) 70. An additional study included medication costs per complication without breaking this out by specific medication 45*Indicated as (non-specific) insulin in study text.†Indicated as group of oral antidiabetic medications (non-specified per drug) in study text (excluding medicines for comorbidities such as CVD); any specifications included as footnotes here.‡Includes lipid-lowering medicines, antiplatelet, antihypertensive drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also included other medicines: antibiotics35; pain relief/anti-inflammatory drugs35; gliflozin class drugs68; sulfonylureas68 69; metformin combinations (with glibenclamide,46 with DPP4i) 70. An additional study included medication costs per complication without breaking this out by specific medication 45*Indicated as (non-specific) insulin in study text.†Indicated as group of oral antidiabetic medications (non-specified per drug) in study text (excluding medicines for comorbidities such as CVD); any specifications included as footnotes here.‡Includes lipid-lowering medicines, antiplatelet, antihypertensive drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also included other medicines: antibiotics35; pain relief/anti-inflammatory drugs35; gliflozin class drugs68; sulfonylureas68 69; metformin combinations (with glibenclamide,46 with DPP4i) 70. An additional study included medication costs per complication without breaking this out by specific medication 45…”
Section: Resultsmentioning
confidence: 99%
“…It can have a negative effect on the T2DM patient, their family/carer, the health system and the economy. In patients, it can adversely affect their adherence to medicines, quality of life and life expectancy, can lead to suboptimal blood glucose control and hospital admissions, and can increase severe hypoglycaemia risk and healthcare costs [10][11][12][13][14]. Studies conducted in different diabetes (including T2DM) populations and settings have reported a range of polypharmacy prevalence figures (6-85%) [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…As far as the latter is concerned, it is also licit to attribute the low adherence rates to an absence of glycemic control, in spite of the pharmacological treatment (a range of 18-75% for HbA1c) (15,65-69). These factors substantially contribute to increasing costs for individuals, communities, and the State in terms of money, quality of life, and lives themselves (61,62,67-70).…”
Section: Discussionmentioning
confidence: 99%